IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2015 TENTANG BADAN PERMUSYAWARATAN DESA - Febri Yuliani, Heri Siswoyo, Sujianto, (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of Regional Regulation Number 3 of 2015 concerning VillageConsultative Bodies. The purpose of this study was to find out how the implementation ofRegional Regulation No. 3 of 2015 Indragiri Hilir Regency. This study uses a qualitativedescriptive research method approach. Primary data is obtained directly through interviews frominformants, namely the village head, Village Secretary, Village Consultative Body (BPD),Community Leaders and the community. The results of this study indicate that the implementationof Regional Regulation No. 3 of 2015 in Indragiri Hilir District implementing the VillageConsultative Body's tasks has not yet achieved the expected results, there are still some tasks thathave not been carried out by the Village Consultative Body. This happens because of the ability ofresources both human resources and financial resources that have not been supported, so thatRegional Regulation No. 3 of 2015 in Indragiri Hilir Regency has not been able to be fullyimplemented.